Topical issues of the realization and protection of human rights in the practice of smart contract technology application - S. S. Kuznetsova (Правоприменение)
The subject and the aim of the study. The article analyzes the approach to smart contract technology, which is reflected in the scientific literature and legislation of Russia and foreign countries, formulates the advantages and disadvantages of a smart contract that affect the implementation and protection of certain constitutional rights, including freedom of contract, the right to protect, the right to manage personal data.Methodology. Guided by formal dogmatic and comparative law methods in research, the author formulates approaches to the concept of a smart contract that has been developed in the practice of foreign countries and deduces how each of the approaches affects the implementation of constitutional human rights. The paper notes that the use of a smart contract based on the federal blockchain does not allow the full implementation of such rights as freedom of contract, the right to self-defense, and the right to manage personal data. In addition, the transnational nature of smart contracts usage, their pseudonymity and failure to unified concept of legal regulation create obstacles to the effective implementation of the right to judicial protection.The main results. The practice of legal regulation of smart contracts in foreign countries, aimed at minimizing the negative consequences of the use of technology is considered. Some countries follow to the concept of recognizing a smart contract as a form of contract (Italy, United States, Republic of Belarus) and a way of guaranteeing fulfilment of obligations (China, Italy, Republic of Belarus, Russian Federation). The second concept is considered as being the most restrictive for digital progress from one side but being able to guarantee protection of human rights such as right to judicial protection or freedom of contract. The first concept which shows smart contract being a type of contract carries additional risks associated with conclusion of a treaty - inconsistency of the smart contract with the actual will of the parties. The third concept considered smart contract as a type of contract is accepted in the Republic of Malta. The Republic of Malta regulated procedure of voluntary certification for smart contracts that allow to eliminate such threats as violation of human rights and the use of smart contracts for criminal purposes. The experience of legal regulation of smart contracts in the Republic of Malta is recognized as reasonable and effective, however, it is concluded that certification will achieve its goals only if it will be implemented in the legal system of wide range of the countries.Conclusions. It is concluded that despite the fact that the smart contract technology has high potential for its implementation in various fields of social and economic life, the effective implementation of smart contract technology in various spheres of society requires the formation of general legal principles for their application, the definition of areas in which the use of smart contracts is prohibited, as well as the development of international standards for their safe execution.